New insights into the plasma and urinary metabolomic signatures of spontaneously hypertensive rats - Celia Rodríguez-Pérez; Alejandra Vázquez-Aguilar; Oscar Daniel Rangel Huerta; Estefanía Sánchez-Rodríguez; Ángel Gil; Caridad Díaz; Félix Vargas; María D. Mesa (PLoS ONE, 2026)
Background Hypertension is a major risk factor associated with cardiovascular diseases and one of the leading causes of premature death. Metabolomics is a useful tool for studying in vivo metabolic profiles to better understand the pathogenesis of diseases such as hypertension. This work aimed to explore the plasma and urinary non-targeted metabolic profile of 16-week-old spontaneously hypertensive rats (SHR) to identify new metabolomic profiles associated with hypertensive phenotypical characteristics. Methods Plasma and 24-hours urine samples were collected from 10 SHR and 10 age-matched normotensive Wistar-Kyoto 16-week-old male rats. Plasma and urinary metabolic profiles were investigated using high-performance liquid chromatography quadrupole time of flight coupled to mass spectroscopy followed by multivariate statistical analysis. The mummichog pathway enrichment analysis was used to integrate metabolomics data into biological contexts. Results A total of 16 differential metabolites were found in plasma and 13 differential metabolites in urine from SHR compared to normotensive rats. Differences in some microbiota-derived metabolites suggest changes in the gut microbiota associated with hypertension in our experimental model. The mummichog algorithm has recognized that hypertensive metabolism is associated with the altered metabolism of steroid hormones, bile acid, and purines. Conclusions This work highlights the importance of metabolomics as a tool for the identification of biomarkers related to hypertension and its consequences in SHR. The findings suggest that alterations in the metabolism of steroid hormones, bile acids, and purines, as well as metabolites derived from the intestinal microbiota are associated with the presence of hypertension. More research is needed to further understand their role during hypertension.